New strategy models in digital entrepreneurship - Albattat, Ahmad; Hassan, Viana; Valeri, Marco; Yazici, Ayşe Meriç (IGI Global, 2024)
The changing digital landscape has many organizations grappling with the challenge of adapting to unprecedented changes and innovation. The absence of a universally accepted definition of digital strategy exacerbates the complexity, leaving leaders uncertain about how to navigate this journey. Inertia becomes an untenable response to the urgent questions organizations face in a digitized world-how to seize digital opportunities, mitigate threats, and transform traditional values into digital assets.New Strategy Models in Digital Entrepreneurship emerges as the definitive solution for academic scholars seeking clarity and guidance in the realm of digital strategy. The book offers a comprehensive collection of papers that explore traditional paradigms, contemporary approaches, and innovative research methodologies. It serves as a beacon for practitioners, academicians, postgraduate and undergraduate students, and librarians, providing a roadmap for formulating and executing robust digital strategies. From theoretical foundations to the application of innovative business models, the book presents a holistic approach to navigating the complexities of digital transformation.